Damage in extrusion additive manufactured parts: Effect of environment and cyclic loading - Moetazedian, Amirpasha; Gleadall, Andrew; Mele, Elisa; Silberschmidt, Vadim V. (Elsevier, 2025)
With a general cautious attitude regarding the anisotropic properties of upright 3D-printed parts, there is a lack of fundamental understanding of behavior of 3D-printed polymers under cyclic loading condition, which is more representative of real-life applications including biomedical ones. To this date, no study considered the multi cyclic testing of an interface bond between layers. So, to examine this, specially designed specimens were developed with the filament widths varied as printed normal to the direction of printing in order to produce dogbone specimens for cyclic tensile testing with two key aims: (i) to characterise the accumulation of damage adjacent extruded filaments; and (ii) to investigate the effect of testing environment on the degradation of mechanical properties. It was found that cyclic loading of 3D-printed polylactide (PLA) specimens resulted in the accumulation of plastic strain, lowering the ultimate strength and strain at break by less than 10% compared to non-cyclic testing. The strength of specimens tested submerged at 37°C were 50% lower than that of tested in air. PLA was plasticised by water, which increased the strain at fracture by approximately 40%. Incremental loading of specimens increased the energy dissipation as approaching the yield point of the material for both testing environments. Meanwhile, damage estimation from the slope of unloading curves indicated that plasticised polymer accumulated 18.1% more damage at lower strain compared to that of tested in air. Specimens tested in air failed in a brittle manner, while, submerged cyclic testing resulted in an intermediate brittle-ductile fracture by formation of apparent shear lips and striation along the fracture plane. The results of this study provide new understanding of the material behavior under condition close to in-vivo environment.